Effect of salinity and temperature on the determination of dissolved iron-binding organic ligands in the polar marine environment - Genovese, C; Grotti, M; Ardini, F; Kathrin Wuttig; Vivado, D; Cabanes, D; Ashley Townsend; Hassler, C; Delphine Lannuzel (2022)
It is widely accepted that iron (Fe)-binding organic ligands play a crucial role in Fe distribution in the marine environment and thus in Fe biogeochemistry. Although Competitive Ligand Equilibration – Adsorptive Cathodic Stripping Voltammetry (CLE-AdCSV) is a well-established technique to investigate Fe chemical speciation in marine samples, several impediments still need to be addressed. These include the extrapolation of laboratory measurements to in-situ conditions, the harmonization of the analytical procedures used, and the applicability of the methods over salinity ranges wider than seawater ( e.g. , sea ice). This work focusses on the calibration of 2-(2-thiazolylazo)-p-cresol (TAC), salicylaldoxime (SA) and 1-nitroso-2-naphthol (NN), along the salinity range 1–90, and titration of natural samples at two different temperatures (4 °C and 20 °C). The artificial ligand concentration was 10 μM for TAC and 5 μM for SA and NN. Calibrations showed that increasing salinity caused a decrease in the conditional stability constants (logK' Fe’AL ) for NN and SA (although different behaviours were noted for the two species FeSA and FeSA 2 ). Less accuracy was noted using TAC, which behaved inconsistently outside the 21 < S < 35 range, and its use is therefore discouraged in fresh and highly saline waters. Titrations of natural samples showed that only SA covered the salinity range selected, up to 78, and its use is therefore recommended in sea-ice studies. The side reaction coefficient (logα' Fe’AL ) of each artificial ligand was found to be influenced by temperature differently: logα' Fe’SA was higher at lower temperature (4 °C), whereas logα' Fe’SA2 and logα' Fe’NN3 increased with increasing temperature (to 20 °C). Although titrations performed at 4 °C highlighted that the uncomplexed Fe fraction was 14% lower than at 20 °C, with potential consequences on primary productivity, the percentage of natural Fe complexed was >99%. Future investigations should consider the analysis of the samples at a temperature ...